Erratum: TOLEDO, LUÍS FELIPE (2010) Description of a new species of Pseudopaludicola Miranda-Ribeiro, 1926 from the state of São Paulo, Southeastern Brazil (Anura, Leiuperidae). Zootaxa, 2681, 12–25. - Toledo, Luís Felipe (Zootaxa, 2010)
(Erratum)